Rwanda Economic Update, June 2021 : The Role of the Private Sectorin Closing the Infrastructure Gap - World Bank (World Bank, Kigali, 2021)
The Rwanda Economic Update (REU) analyzes recent economic developments and prospects, as well as Rwanda’s policy priorities. The REU is intended for a wide audience of policymakers, business leaders, other market participants, analysts of Rwanda’s economy, and civil society. It draws on data reported by the Government of Rwanda and additional information collected by the World Bank Group in its regular economic monitoring and policy dialogue. Published twice a year, each issue has a special feature spotlighting a particular topic. The 17th edition of REUfocuses on the role of the private sector in closing the infrastructure gap.